Systematic Review Of Research And Development Expenditures And Sustainable Economic Development In Asean Countries - Muhammad Khalid Shahid; Aye Aye Khin; Lim Chee Seong (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2023)
Although numerous researches about the importance of research and development (R & D) for sustainable economic development have been carried out among ASEAN countries, it is challenging to say with certainty that what level of interest is being put on R&D expenditures and sustainable economic development among these countries. The objective of this study is to conduct the systematic review of R & D expenditures and sustainable economic development in ASEAN countries with theoretical and empirical review of the previous studies. This paper grouped previous studies considering economic development based on their results in Four (4) stages i.e. 1) review of previous literature, 2) comparison of growth theories and, 3) developing a concept in light of previous models and at last, 4) the conclusive note related to R&D and economic development among ASEAN countries. Total 163 research articles were considered containing the terms economic development or economic growth and after applying a systematic review process, 14 papers considered as final sample specific to the objective of this study related to economic development among ASEAN countries. The review has shown that most of economist found that previous studies were lack of R&D expenditures in the economic development among ASEAN region countries. This study fills theoretical and empirical gap in the field of R&D-lead economic development among ASEAN and provides a meta-theoretical insight in the concept of sustainable economic development with respect to R&D expenditures.